Ultrafast reflectivity dynamics in bis (n-butylimido) perylene thin films - Mendonca, C. R.; Kandyla, M.; Shih, T.; Aroca, R. F.; Constantino, C. J L [UNESP]; Mazur, Eric (My University, 2008)
Using pump-probe reflectometry, we study the ultrafast excited-state dynamics in thin films of BuPTCD, an organic semiconductor, deposited on gold nanoparticles. We observe depletion of the ground state and excited state absorption after photo-excitation. © 2008 Optical Society of America.
Keywords: Absorption; Dynamics; Electromagnetic waves; Electron optics; Excited states; Lasers; Nanostructured materials; Quantum electronics; Reflection; Thick films; Thin films; Electro-optics; Laser science; Ultra-fast; Semiconductor lasers